WAAC-3 Acute Bacterial Meningeoencephalitis in Stranded Juvenile Green Turtle (Chelonia Mydas) in Gerokgak Beach, Buleleng Regency, Bali - Ida Ayu Dian Kusuma Dewi; Yustisia Semarariana; I Bagu Made Bhaskara; Dwi Suprapti; Maulid Dio Suhendro; Fidry R Ikhwan (Hemera Zoa, 2018)
Bacterial infection in sea turtles has been rarely recorded as a primary disease in wild turtles. Non-specific clinical sign and presumably interrelation with parasitic disease as the primary cause of illness in wild sea turtle are more common particularly affecting the respiratory and integumentary system(George, 1996). Bacterial infection that reach the brain are usually preceded by heavy and chronic infestation of neuroparasitic and cardiovascular parasitic infection in green turtle (Raidal, Ohara, Hobbs, & Prince, 1998). Furthermore, report on acute bacterial meningoencephalitis which lead to sudden death has never been reported before. Interestingly, acute death in stranded sea turtle is usually attributed with bio toxin and human-related trauma(Orós, Torrent, Calabuig, & Déniz, 2005).